2010
DOI: 10.2516/ogst/2009083
|View full text |Cite
|
Sign up to set email alerts
|

HyGenSys: a Flexible Process for Hydrogen and Power Production with Reduction of CO2Emission

Abstract: Résumé -HyGenSys : un procédé flexible de production d'hydrogène et d'électricité avec réduction des émissions de CO 2 -Cet article présente les développements récents d'HyGenSys, nouvel éco-procédé de conversion du gaz naturel en hydrogène et électricité. Le concept combine un réacteur-échangeur spécifique de reformage à la vapeur avec une turbine à gaz. En fait, la chaleur nécessaire pour la réaction de reformage à la vapeur provient des fumées pressurisées produites dans une turbine à gaz au lieu d'un four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This catalyst has previously been reported for natural gas reforming. 24 The porous structure of the as-received fresh catalyst (before activation) was determined by N 2 adsorption. The adsorption isotherm (not shown) can be ascribed to the type IV isotherm of the International Union of Pure and Applied Chemistry (IUPAC) classification, showing the usual hysteresis loop between the adsorption and desorption curves typical of mesoporous materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This catalyst has previously been reported for natural gas reforming. 24 The porous structure of the as-received fresh catalyst (before activation) was determined by N 2 adsorption. The adsorption isotherm (not shown) can be ascribed to the type IV isotherm of the International Union of Pure and Applied Chemistry (IUPAC) classification, showing the usual hysteresis loop between the adsorption and desorption curves typical of mesoporous materials.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the catalyst composition (as determined by the manufacturer) as well as its porous structure data (determined by N 2 adsorption, using the same analyzer and in the same conditions as those used for the dolomite measurements). This catalyst has previously been reported for natural gas reforming …”
Section: Resultsmentioning
confidence: 99%
“…This issue is industrially highly relevant since most industrial processes are typically performed above ambient pressure. Examples include H 2 and syngas plants or technologies such as autothermal reforming or dry reforming, in which methane and other hydrocarbons are reformed or partially oxidized to produce H 2 and CO [6]. Natesan and Zeng [4] demonstrated that the Ni-based alloy 602 CA is far more prone to develop MD at elevated pressures than at ambient pressure, with the same C activity in both gases.…”
Section: Introductionmentioning
confidence: 99%